2018
DOI: 10.2147/dmso.s154978
|View full text |Cite
|
Sign up to set email alerts
|

Influence of <em>FTO</em> rs9939609 polymorphism on appetite, ghrelin, leptin, IL6, TNF&alpha; levels, and food intake of women with morbid obesity

Abstract: BackgroundThe fat mass and obesity-related (FTO) gene has a strong relationship with obesity, extreme obesity and inflammatory state, and may also be associated with food intake regulation.ObjectiveThe aim of the present study was to evaluate the influence of the rs9939609 single-nucleotide polymorphism of the FTO gene on appetite, ghrelin, leptin, interleukin 6 (IL6), tumor necrosis factor α (TNFα) levels and food intake of morbidly obese women.Materials and methodsThe study comprised 70 women, aged between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 47 publications
0
29
1
1
Order By: Relevance
“…whereas we adopted a multivariate-adjusted approach to our data analysis. Interestingly, recent studies have reported lower postprandial total ghrelin concentrations in AA compared to AT and TT individuals (Magno et al 2018;Melhorn et al 2018), and postprandial hunger ratings were either similar between genotype groups (Melhorn et al 2018) or were lower in AA individuals (Magno et al 2018). These findings were observed despite the AA individuals exhibiting higher energy intake during an ad libitum buffet (Melhorn et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…whereas we adopted a multivariate-adjusted approach to our data analysis. Interestingly, recent studies have reported lower postprandial total ghrelin concentrations in AA compared to AT and TT individuals (Magno et al 2018;Melhorn et al 2018), and postprandial hunger ratings were either similar between genotype groups (Melhorn et al 2018) or were lower in AA individuals (Magno et al 2018). These findings were observed despite the AA individuals exhibiting higher energy intake during an ad libitum buffet (Melhorn et al 2018).…”
Section: Discussionmentioning
confidence: 90%
“…However, rs9939609 was associated with increased TNFa in Mexican women with gestational diabetes (Saucedo et al, 2017). The impact of rs9939609 on the fasting and postprandial level of IL-6 and TNFa in Brazilian women revealed that, in the fasting stage, levels of IL-6 and TNFa were similar for the A and T risk alleles but in the postprandial period, while TNFa was not altered in individuals with AA genotype compared to TT and TA genotypes, the serum levels of IL-6 and ghrelin were low and those of leptin were high (Magno et al, 2018). Ethnicity is likely to have an effect on the variation in association of FTO with inflammatory markers and investigating these variants may offer a better understanding of their role in the obesity epidemic affecting the world and particularly countries such as Kuwait and others in the Gulf region.…”
Section: Discussionmentioning
confidence: 99%
“…Rutters et al found FTO A allele to be associated with higher BMI and leptin levels at the age of 12, with the association being stronger at the age of 17 [44]. Magno et al showed that those with the AA genotype had higher values of leptin than those with TT and AT [45]. Yet others have reported the expression of Kiss1 gene (gene that produces kisspeptin) may be induced by leptin [46,47].…”
Section: Discussionmentioning
confidence: 99%